S100A8-mediated metabolic adaptation controls HIV-1 persistence in macrophages in vivo - Fernando Real; Aiwei Zhu; Boxin Huang; Ania Belmellat; Alexis Sennepin; Thomas Vogl; Céline Ransy; Marc Revol; Riccardo Arrigucci; Anne Lombès; Johannes Roth; Maria Laura Gennaro; et al. (Nature Communications, 2022)
HIV-1 eradication is hindered by viral persistence in different cell reservoirs, including circulatory CD4+ T-cells and tissue-resident macrophages. Here, by analyzing male genital mucosa from cART-suppressed HIV1-infected individuals, Real et al. show that M4 macrophages represent the major macrophage HIV-1 reservoir in this tissue. These macrophages have an inflammatory IL1R+S100A8+MMP7+M4-phenotype, and contain transcriptionally active HIV-1, which reactivate infectious virus production from viral latency in response to autocrine/paracrine S100A8-mediated glycolysis.